2020
DOI: 10.14527/pegegog.2020.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reciprocal teaching on reading comprehension, retention on learning and self-efficacy perception

Abstract: This study was carried out to test the effects of reciprocal teaching on reading comprehension skills, learning retention and self-efficacy perception of reading comprehension. Research was conducted in 4th grade Turkish lessons of a primary school located in the Central Anatolia region of Turkey with experimental and control groups of 25 randomly assigned students. Experimental method was used in the research and findings were supported with qualitative data. Data were collected through the Reading Comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(99 reference statements)
1
2
0
Order By: Relevance
“…It is in line with Kula and Budak (2020) who also explained the students' perceptions toward reciprocal teaching in reading comprehension comprehension. They ISSN 0216 -809X (Print) ISSN 2685 -4112 (Online) found that in implementing reciprocal teaching in reading comprehension class, the students had been given chances to work with their group member to exchange ideas.…”
Section: The Benefits Of Reciprocalsupporting
confidence: 84%
See 1 more Smart Citation
“…It is in line with Kula and Budak (2020) who also explained the students' perceptions toward reciprocal teaching in reading comprehension comprehension. They ISSN 0216 -809X (Print) ISSN 2685 -4112 (Online) found that in implementing reciprocal teaching in reading comprehension class, the students had been given chances to work with their group member to exchange ideas.…”
Section: The Benefits Of Reciprocalsupporting
confidence: 84%
“…Moreover, Kula and Budak (2020) also desrcribed the students' perceptions considering reciprocal teaching in reading comprehension comprehension. With 25 students as the participants at primary school in Turkey, this study aims to explore students' perceptions about reciprocal teaching by dividing students into some groups.…”
Section: Students' Perceptions Of Reciprocal Teachingmentioning
confidence: 99%
“…Noise is also a negative condition in other research results in which mind games are played (Demirel, 2015). It is possible to come across similar noise-related results not only as a special case for mind games but also in other studies where students work in groups (Kula & Budak, 2020). In fact, one of the reasons why there is noise in the classroom during group work and playing games may be the flow of students.…”
Section: Discussionmentioning
confidence: 54%
“…It has been stated that educators and educational institutions have not implemented a comprehensive approach to improving students' retention [17]. According to other reports, low concept mastery some of which was brought on by incorrect learning outcomes influences low student retention as well [19]. Consequently, when knowledge about a particular concept or topic is not preserved, poor performance and accomplishment may follow.…”
Section: Introductionmentioning
confidence: 99%